2017
DOI: 10.1111/bju.13861
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of a new urinary biomarker‐based risk score compared to standard of care in prostate cancer diagnostics – a decision analytical model

Abstract: Based on the currently available evidence, the reduction of over diagnosis and overtreatment due to the use of the SelectMDx test in men with PSA levels of >3 ng/mL may lead to a reduction in total costs per patient and a gain in QALYs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 22 publications
2
82
0
1
Order By: Relevance
“…The novel diagnostic strategies that were compared to PSA-based testing alone included PSA plus Prostate Health Index (PHI) testing (18,27,31), SelectMDx testing (21,24) and Urinary Proteome Analysis (UPA-PC) testing (19). The de nitions of these biomarker tests are given in Appendix 3, Table 1.…”
Section: Strategies Compared -Biomarkersmentioning
confidence: 99%
See 4 more Smart Citations
“…The novel diagnostic strategies that were compared to PSA-based testing alone included PSA plus Prostate Health Index (PHI) testing (18,27,31), SelectMDx testing (21,24) and Urinary Proteome Analysis (UPA-PC) testing (19). The de nitions of these biomarker tests are given in Appendix 3, Table 1.…”
Section: Strategies Compared -Biomarkersmentioning
confidence: 99%
“…The modelled prevalence of prostate cancer varied from 10.9% (18) to 66.7% (31), but was usually between 24-30%. Several studies reported the percentage of prostate cancers assumed to be high grade or signi cant (24) (33) (18,21), ranging from 26%(18) to 51.2% (24).…”
Section: Patient Populationmentioning
confidence: 99%
See 3 more Smart Citations